Investigation of milk-fat lamb production practices for Western Kansas, Colby - Menzies, C.M.; Banbury, Evans E.; Elliott, H. (Kansas Agricultural Experiment Station, 2011)
The ewe flock is handled in an early lambing program with the breeding season beginning around June 1 and ending September 1. All lambs are sold as milkfat lams during the spring and early summer. Two separate tests were made during 1965-66. (1) a study to determine the value of different rations for creep-feeding lams and (2) a study determining the various treatments and rations for flushing ewes.
Keywords: Lamb; Milk fat lambs; Creep feed; Rations